A potencialização dos homicídios no contexto do espaço social: o caso de Belém do Pará - GOMES, Monique Kelly Tavares (Universidade Federal do Pará, 2014)
This dissertation aims to present the factors that have boosted the incidence of homicides in the social space context in Belém do Pará, between 2007 and 2010. With this objective in mind, the mapping of homicides was used to assess the dynamics of this violent crime. Based on the specialization of occurrences, it was possible to observe that its distribution is not uniform, and over the years between 2004 and 2007, it had been more concentrated in some areas than in others. Some city districts also known as “bairros” stood out because the result social conflicts ended up in high homicide rates. Under this context and based on explanations put forth in publications specialized on the subject, we concluded that the precarious nature or lack of public services pertaining to the Municipality are factors that might be boosting the homicide rates in some “bairros”. In such places, it is clear that the performance of the Democratic State that is Governed by Law sis not sufficient to guarantee fundamental rights, such as life, liberty and equality and the citizen’s safety.